2014
DOI: 10.1101/gad.237479.114
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced cohabitation of active immunoglobulin genes from three different chromosomes in transcription factories during maximal antibody synthesis

Abstract: To understand the relationships between nuclear organization and gene expression in a model system, we employed three-dimensional imaging and chromatin immunoprecipitation (ChIP)-chromosome conformation capture (3C) techniques to investigate the topographies of the immunoglobulin (Ig) genes and transcripts during B-cell development. Remarkably, in plasma cells, when antibody synthesis peaks, active Ig genes residing on three different chromosomes exhibit pronounced colocalizations in transcription factories, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 33 publications
4
50
1
Order By: Relevance
“…This is consistent with numerous studies linking transcriptional co-regulation to spatial clustering of the relevant genes and their cis-regulatory elements [26][27][28][29][30][31][32] around the nucleoplasmic supra-molecular entities that harbor most nuclear transcription-around transcription factories [19].…”
Section: Large-scale Reorganization Of Higher-order Chromatin Structusupporting
confidence: 88%
“…This is consistent with numerous studies linking transcriptional co-regulation to spatial clustering of the relevant genes and their cis-regulatory elements [26][27][28][29][30][31][32] around the nucleoplasmic supra-molecular entities that harbor most nuclear transcription-around transcription factories [19].…”
Section: Large-scale Reorganization Of Higher-order Chromatin Structusupporting
confidence: 88%
“…Using our published techniques (15, 16, 30), pre-B cells were processed for 3D DNA FISH. Briefly, probes for 3D FISH were prepared from bacterial artificial chromosomes (BACs).…”
Section: Methodsmentioning
confidence: 99%
“…To make probes for each slide, 1 μg BAC DNA samples were labeled by nick translation with ChromaTide Alexa Fluor 488–5-deoxyuridine triphosphate (dUTP), ChromaTide Alexa Fluor 594–5-dUTP (Invitrogen), or Cy5-dUTP (GE Healthcare). Hybridization conditions were as described previously (15, 16, 30). FISH signals were analyzed by Leica TCS SP5 confocal microscopy with Z slice-sections separated by 0.3 μm, and the center-to-center distances between different hybridizing signals were measured using a plug-in of ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining coupled with DNA/RNA FISH revealed that actively transcribing immunoglobulin genes (IgK, IgH, and IgJ) from three different chromosomes colocalize at TNs, as marked by RNAPII (74). Further ChIP-3C-seq experiments with antibodies against RNAPII demonstrated that enhancer elements act in trans (interchromosomally) at these TNs to promote both the positioning of the different genes and their activation.…”
Section: Transcription Neighborhoodsmentioning
confidence: 96%
“…These immunoglobulin TNs were also found positioned in the ICD. It was speculated that the existence of the TNs in this space allowed for rapid and efficient export of immunoglobulin transcripts out of the nucleus for translation, demonstrating additional functionality of TNs in the ICD (74).…”
Section: Transcription Neighborhoodsmentioning
confidence: 99%